MDRO Beijing Consensus Meeting Report: Global burden of multidrug-resistant organisms' current antimicrobial resistance problems in Asia-Pacific. Issue 1 (March 2014) - Gould, I.M.; Wang, Gui-Qiang; Wu, Jiunn-Jong; Lim, V.K.E.; Hutchinson, Jim; Walsh, Tim; Turnidge, John
Abstract: The International Society of Chemotherapy's Working Groups on Antibiotic Resistance and Antibiotic Stewardship convened a half-day workshop on the burden of multidrug-resistant organisms in the Asia-Pacific. This short review is a summary of their discussion and conclusions.